The Occurrence and Infectivity of Arbuscular Mycorrhizal Fungi in Inoculated and Uninoculated Rhizosphere Soils of Two-year-old Commercial Grapevines - Meyer, A.H.; Botha, A. Botha; Valentine, A.J.; Archer, E.; Louw, P.J.E. (South African Journal of Enology and Viticulture, 2017)
Arbuscular mycorrhizal (AM) fungal populations present in the rhizosphere of vine roots in the vineyards of a commercial farm in the Stellenbosch Region were investigated using microscopic analyses. AM root colonisation levels of between 70% and 90% were found in both grapevine roots that were previously artificially inoculated with commercial AM inocula, and in uninoculated (control) grapevine roots. The AM fungal isolates in the rhizosphere soil, identified using morphological criteria, belonged to the genera Acaulospora, Gigaspora, Glomus, Sclerocystis and Scutellospora. The majority of species found was not present in the commercial inocula and was either indigenous to the vineyard or originated from the nursery where the vines were obtained. Isolates of Glomus and Acaulospora appeared to be the most abundant. The AM fungal species occurred at a soil phosphorus (P) concentration of up to 80 mg/kg P and a soil pH (KCl) that ranged between 5.63 and 6.10. Total spore counts ranged between 1 000 and 3 779 spores/100 g dry soil. In accordance with literature, lower spore concentrations were recorded for the heavier soil types with no cover crop system, compared with the sandy soil type on which cover crops were sown annually.